The Question of Responsibility: (De-)Peripheralising Rural Spaces in Post-Socialist Estonia - Plüschke-Altof, Bianka (European Spatial Research and Policy, 2018)
Recent studies on socio-spatial polarization and post-socialist spaces increasingly propose the use of postcolonial theory. Following this proposal, the paper attempts to make the decolonial approach fruitful for studying the crucial role that discourses play for rural peripheralisation processes in post-socialist Estonia. It shows that the Estonian discourses on peripheries manifest in a struggle between neoliberalism and interventionism as two competing regional development models that promote either self- or state responsibility for dealing with peripheralisation. Despite their differences, both models build on the same notion of modernity, as the colonial history associated with socialist modernity renders alternative models obsolete.